2016
DOI: 10.1111/jfpe.12356
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Upstream Process Parameters for Enhanced Production of Thermostable Milk Clotting Enzyme from Bacillus Subtilis MTCC 10422

Abstract: The process protocol of high titer milk clotting enzyme (MCE) production from Bacillus subtilis was delineated through optimizing different energy sources and growth conditions like incubation period, temperature and pH. The culture broth showed maximum production of MCE at pH 6.0 and temperature 40C after 48 h of incubation with the yield of 191.55 U/mL. Quantitative comparison of MCE activity before and after optimization revealed 7.46-fold increase in MCE production after the process conditions were standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…1E), and it decreased at higher speeds due to increased mechanical shear force that was not conducive to cell growth (Hashem, 2000;Narwal et al, 2017). Proper agitation of culture would facilitate MCA by letting in more air, therefore oxygen, but some other studies presented otherwise different results, that still culture would yield a higher MCA (Hashem, 2000;Narwal et al, 2017;Sun et al, 2014), which was possible due to the differences in the nature of strains. He et al (2012) indicated that the initial pH of growth medium strongly affected enzyme reaction and transport of various components across the cell membrane, thus the MCA of B. methanolicus LB-1.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…1E), and it decreased at higher speeds due to increased mechanical shear force that was not conducive to cell growth (Hashem, 2000;Narwal et al, 2017). Proper agitation of culture would facilitate MCA by letting in more air, therefore oxygen, but some other studies presented otherwise different results, that still culture would yield a higher MCA (Hashem, 2000;Narwal et al, 2017;Sun et al, 2014), which was possible due to the differences in the nature of strains. He et al (2012) indicated that the initial pH of growth medium strongly affected enzyme reaction and transport of various components across the cell membrane, thus the MCA of B. methanolicus LB-1.…”
Section: Resultsmentioning
confidence: 98%
“…1C). Extension of fermentation time accompanied with gradual depletion of nutrients in the medium, preventing normal metabolism of microorganisms and MCA (Narwal et al, 2017). The MCA reached the maximum at 35°C (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…subtilis MTCC 10422 isolated from soil was maintained on modified yeast extract milk agar media (YEMA) supplemented with sucrose, at 4°C by transfer onto a fresh medium after every 2-4 weeks. The enzyme was produced under liquid state fermentation (LSF) conditions in yeast extract milk media (pH 6.0, temperature 40°C) [9]. The bacterial growth was allowed for 48h of incubation.…”
Section: Cultivation and Productionmentioning
confidence: 99%
“…Although milk clotting enzymes (MCEs) have many applications in cheese industry and recently authors [9,10] have reported on their production and purification, yet their commercial exploitation can only be realized after immobilization. In the present investigation, attention hasbeen focused on encapsulation of MCE using biopolymers like alginate which has numerous applications in food processing, textile industry and pharmaceutical sector.…”
Section: Introductionmentioning
confidence: 99%